EFFCTS OF ADDITIVES, METHODS AND NUMBER OF APPLICATION ON ACTIVITY OF GLYPHOSATE CONTROLING FOR Dichanthium annulatum (Forsk) stapf. GROWTH IN SUGARCAN FIELDS - AL-Wagga , Adnan Hussein; Al-juboory, Baqir Abdkhalf (Diyala Agricultural Sciences Journal, 2013)
This research was conducted in the fields of the General Company of sugar – factory and farm of sugar cane , Missan , during the season of 2001 / 2002 , to control Dichanthium annulatum (Forsk) stapf , growing in the root of the sugar cane Saccharum officinarum L. fields .Use by different rate of glyphosate in a direct application by using wipe or spray method, different rate of the additive of 1% [Urea + (NH4)2SO4] solution , and different times of application. The experiment was set out as factorial design in randomization complete block design in split – plot design with three replicates. Treatments of number of applications during the season, were considered as main – plot , while the control were considered as a sub-plot . The results showed that The treatments and number of applications were significantly affected in degree of weed killing up 82.91 , at 115 , 190 day and the regrowth of the weed in end season after application Treatment of 1 : 4 glyphosate : water + 1% of the [Urea + (NH4)2SO4] solution , which applied was the most affective on all the studied characteristics of weed plants. Treatments significantly affected all the studied characteristics on crop plants (except of stem diameter). using wipe application spray application , were most effective in weed control as a direct methods for glyphosate application , with no significant damage on the crop plant.